Vulnerability of Nigerian maize traders to a confluence of climate, violence, disease and cost shocks - Vargas, Carolina M.; Liverpool-Tasie, Lenis Saweda O.; Reardon, Thomas (Emerald Publishing Limited, 2025)
Purpose We study five exogenous shocks: climate, violence, price hikes, spoilage and the COVID-19 lockdown. We analyze the association between these shocks and trader characteristics, reflecting trader vulnerability.